The role of the generalized motor program and forward modeling at the control of quick discrete movement - Vass, Z. (International Journal of Computer Science in Sport, 2002)
In the last decade numerous theories come out in connection with motor learning and motor control (Richard A. Schmidt, Kawato, Gomi). In these theories the concept of motor program is used to interpret the preparation and initiation of quick, discrete movements. According to the given theories the process of motor learning is interpreted as general rule learning. This article put the emphasis on the role of generalized motor program and forward modeling, in the framework of the movement analysis of a quick, discrete task. The subjects were asked to make a quick extention-flexion in their elbow joint using their palm to generate a vacuum to blow out a candle without any direct connection with the flame. The experimental order and the quick execution of the movement assured to analyze the connection between the generalized motor program and the forward model. 6 sport university students were participated in this experiment. Their age is between 22-27 and all of them are active as sportsmen. One hand the aim of this experiment is to determine the successful movement execution criteria`s with movement analysis technique. And the other hand to work out such a measurement method to indicate the relation between generalized motor program and forward model. Our hypothesis is the successful movement execution depends on the precise anticipation of the required movement parameters, and on the basis of the provided parameters the movement will be executed by the generalized motor program. On the basis of our result the main criteria of the successful execution is the wrist joint timing during the movement. It indicates that the chosen of the right generalized motor program was correct but the forward model was not able to provide the correct parameters in connection with timing of the wrist joint and the movement dynamics.